Dynamics of the spread of SARS-CoV-2 variants and clades (Eurasian Journal of Ecology, 2022)
In the XX century, discovered Human Coronavirus, including HCoV-229E, HCoV-NL63 from the genus Alphacoronavirus and HCoV-OC43, HCoV-HKU1 from the genus Betacoronavirus have long been considered insignificant pathogens for humans, causing infections in the upper respiratory tract in adults. However, at the beginning of the XXI century, highly pathogenic coronaviruses of the severe acute respiratory syndrome (SARS-CoV) and coronavirus of the Middle East respiratory syndrome (MERS-CoV) caused global epidemics and eventually led to death. In December 2019, Wuhan, China, revealed another new Human CoV-2019. On March 11, 2020, WHO announced a new global pandemic of Human CoV – 2019 due to its global spread within a short time. As of September 23, 2021, according to WHO data, a total of 229,858,719 confirmed cases of COVID-19 and 4,713,543 deaths were registered. The emergence and global spread of SARS-CoV-2 coronavirus variants remain largely unknown. But the spread of COVID-19 around the world increases interest in the disclosure of genomic mutations of a new variant of the coronavirus SARS-CoV-2. Data on the epidemiology of diseases, including the number of cases and mortality in different parts of the world and the Republic of Kazakhstan, are presented. The schematic nomenclature of GISAID, Nextstrain, and Pango lines is compared. The sequence of the SARS-CoV-2 genome submitted to the GISAID database for the Republic of Kazakhstan was analyzed concerning genomic clades and their geographical, age and gender distribution.Key words: COVID-19, SARS-CoV-2, clade.